Controlling Two Chambers Tank Debit By Ethernet With Proportional Integrative Control Method - Adnanqays G. Riyadhi; Erwin Susanto; Ig. Prasetya Dwi Wibawa (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2016)
This paper proposes a proportional integrative control method for two chambers tank by Ethernet using Arduino. An Ethernet module was used for data communication between PC and twin tank. An ultrasonic sensor was mounted in top of two chambers tank to measure a height that can be converted to calculate the debit of the water. We make a dynamic model of the twin tank using linearization model. Then, from the linearized model, we control the debit of the twin tank using proportional integrative (PI) controller to meet required responses.